Ideology and Solidarity: A Portrait of Japanese and Indonesian Intellectual Relations as Recorded in Jawa Kantei Yowa by Asano Akira - Purnomo, Antonius Rahmat Pujo (KIRYOKU, 2024)
This research aims to discover the relationship between Japanese and Indonesian intellectuals during the Japanese military occupation of Indonesia, as recorded by Asano Akira during his assignment in Indonesia in 1942. Serving as members of the Propaganda Division in Indonesia, these Japanese intellectuals had to recruit and collaborate with Indonesian intellectuals to further Japan's military objectives in the Greater East Asia War. The method used in this research is qualitative, employing textual analysis. The research reveals that Asano's interest in the ideas of Arthur Schopenhauer and Okakura Tenshin on asceticism, self-denial, simplicity, and Eastern aesthetics nurtured his Eastern ideological perspectives. It was from this ideology that he eventually came to feel solidarity with his fellow Asians oppressed by Western domination. Therefore, this sense of ideology ultimately led him to establish friendships and cooperate with Indonesian intellectuals while serving in the Propaganda Division of Japanese Military Government.